Transarterial chemoembolization with drug-eluting beads in hepatocellular carcinoma - Nam, Hee Chul; Jang, Bohyun; Song, Myeong Jun (World journal of gastroenterology : WJG, 2016)
Transarterial chemoembolization (TACE) is a widely used standard treatment for patients with hepatocellular carcinoma (HCC) who are not suitable candidates for curative treatments. The rationale for TACE is that intra-arterial chemotherapy using lipiodol and chemotherapeutic agents, followed by selective vascular embolization, results in a strong cytotoxic effect as well as ischemia (conventional TACE). Recently, drug-eluting beads (DC Beads ) have been developed for transcatheter treatment of HCC to deliver higher doses of the chemotherapeutic agent and to prolong contact time with the tumor. DC Beads can actively sequester doxorubicin hydrochloride from solution and release it in a controlled sustained fashion. Treatment with DC Beads substantially reduced the amount of chemotherapeutic agent that reached the systemic circulation compared with conventional, lipiodol-based regimens, significantly reducing drug-related adverse events. In this article, we describe the treatment response, survival, and safety of TACE used with drug-eluting beads for the treatment of HCC and discuss future therapeutic possibilities.